Pelaksanaan Praktek lapangan Industri (PLI) Pada Mahasiswa Jurusan Kesejahteraan Keluarga Fakultas Teknik Universitas Negeri Padang - almi, nora; adriani, adriani; idrus, yenni (Journal of Home Economics and Tourism, 2013)
Abstract This study aims to describe the implementation process Field Industrial (PLI)Faculty of Engineering, Department of Family Welfare Padang State University. This type ofresearch "quantitative descriptive" that describe, explain and interpret the data as it is. Thepopulation in this study were students of the Faculty of Engineering Department of FamilyWelfare has implemented a PLI ranging from 2008 to the armed forces in 2012 of 60 peopleconsisting of: D3 dressmaking as many as 9 people and S1 PKK concentration dressmakingas many as 51 people. The results of the data analysis showed that the implementation of thePLI students of Department of Family Welfare Faculty of Engineering, UNP, very lowcategory of indicators covering: (1) Stage Pre PLI with a percentage of 4.23%, 2) the stage ofimplementation of PLI with a percentage of 2.94%, (3) Phase Post PLI by 7.2%. From theanalysis of the data is evident that the implementation of the student PLI Programs KKcategorized in groups is very low. Therefore it is recommended to all students of the Facultyof Engineering Department of Family Welfare for the implementation of this Industry Fieldfollowed up again so that execution of Field industry can be categorized as either making theachievement of objectives of the implementation of the PLI. Keywords: Implementation of PLI / PKN, Stage Pre-PLI, PLI Implementation Phase, Phase Post-PLI.